BUREAUCRACY AND GOVERNMENT - Yuliana Keke Febrianti; Zahra Malinda Putri; Adhyatma Wikrama Maheswara (Fakultas Hukum Universitas Lampung, 2022)
The purpose of this paper is that the author tries to explain the concept of bureaucracy and government. In addition, the author also describes the differences between bureaucracy and government in terms of definition, theory, and task. This paper also aims to discuss the position of the bureaucracy in the trias politica system where there is a classification of power, namely the executive, legislative and judiciary. Then, this paper will lead to the administration and implementation of public services. The conclusion from this paper is that government and bureaucracy are two different things and bureaucracy can become its own entity outside of the executive, legislative and judiciary and those in charge of providing public services are the bureaucrats, not the government, although actually bureaucrats and government have different roles in responsibility to deliver public service.